DINAMIKA EKSISTENSI JARINGAN DAN GERAKAN KELOMPOK ISLAM RADIKAL INDONESIA - Anwar, Saeful; Shidiq, Agus Sholahudin (At-Tuhfah : Jurnal Studi Keislaman, 2021)
This article entitled the dynamics of the existence of a network of radical Islamic group movements of Indonesia, tried to give an overview of the initial group that did the first Islamic radicalism in Indonesia, namely the Padri movement do violence not only against people outside of Islam, but also against fellow Muslims who do not want to follow their teachings. Violence and such action is not necessarily the case, but more refer to the movement and the view of Saudi Arabia wahabisme idiologis. The radical Islamic movement in post-independence Indonesia itself appeared since the Islamic Sharia enforcement of exacting formalist formally in the Constitution of Indonesia and want the formation of Indonesia into an Islamic State. in this movement the TII/leading kartosoewiryo in West Java and continues in some areas of indonesia. The idea of radical Islam in Indonesia is actually heavily influenced by the views of Islamic scholars such as Ibn Taymiyyah, Muhammad ibn Abdul Wahhab and also radical Islamist thinker Sayid Qutb Muslim Brotherhood Egypt through Ma'alim fi at Thorieq, Shaykh Abdullah Azzam in his work entitled Ayatur Rahman fi Jihadi Afghanistan with the concept of staging, and Osama bin Laden who then managed to influence the muslim activists Indonesia to go to Jihad to Afghanistan.